Intangible assets and integrated management systems - Linkova, Helen Yu. (Уманський державний педагогічний університет ім. Павла Тичини, 2019)
The purpose of the research. It is established that in order to enter new markets and increase the competitiveness of goods in the international market in the conditions of information economy and distribution of intangible assets for domestic enterprises, the role of integrated management systems is increasing. Discovered – The purpose of the study is to analyze the challenges for Ukrainian enterprises in the times of European integration, which requires solving the problems related to the definition of an algorithm for the implementation of international quality standards and mechanisms for assessing the productivity of their use. Methodology. In this work a retrospective analysis of quality management systems at the enterprise is carried out, the results of which revealed the evolutionary components of the quality requirements and the structures of its implementation at the enterprise: input control of raw materials; production processes; international standards; environmental and social management; security of activity and information. Results. The basic world tendencies of economic development are revealed: increasing of global competition, growth of the sphere of services, acceleration of scientific and technological progress, internationalization of financial markets. Characteristics of the modern economy of Ukraine: resource structure of exports; a small component of intangible assets; static attitude to quality. The classification of intangible assets of the enterprise by assets and competencies as a basis for accelerating the process of obtaining the effect of economic activity. Thus, for the implementation of the strategy of entering the European markets, domestic enterprises need to activate the management of the formation of potential capabilities of the enterprise through the development of staff competencies for quality, management systems and negotiation activities to attract additional investments, as well as the adoption of quality standards. Based on the study of the evolution of quality management concepts at the enterprise, the process of integration of management systems is proposed. Integrated management tools (affinity, relationships, lead times): maximize the synergistic effect of integration. Practical meaning. It is established that the spread of integrated management systems will allow: consumers – to get the product with the maximum combination of price and quality; to business owners – to form a systematic attitude of staff to quality, to partners – to reduce the risks of implementation of agreements; to society – to obtain additional sources of funding by increasing export revenues from processing industries and improving environmental and safety performance. Prospects for further research. The direction for further research on the introduction of integrated management systems is proposed – the search for economic-mathematical models that optimally combine internal tangible assets and intangible assets that fall outside the competence of an individual enterprise.

Мета статті. В роботі встановлено, що з метою виходу на нові ринки збуту та підвищення конкурентоспроможності товарів на міжнародному ринку за умов інформаційної економіки та поширення нематеріальних активів для вітчизняних підприємств зростає роль інтегрованих систем управління. Виявлено – метою дослідження є аналіз викликів для підприємств України за часів Європейської інтеграції, що потребує вирішення завдань, пов’язаних з визначенням алгоритму запровадження міжнародних стандартів якості та механізмів оцінки продуктивності їх використання. Методологія. В роботі проведено ретроспективний аналіз систем управління якістю на підприємстві, за результатами якого виявлено еволюційні складові вимог до якості та структур її реалізації на підприємстві: вхідний контроль сировини; виробничі процеси; міжнародні стандарти; екологічний та соціальний менеджмент; безпека діяльності та інформації. Результати. З’ясовано основні світові тенденції економічного розвитку: посилення глобальної конкуренції, зростання сфери послуг, прискорення науково-технічного прогресу, інтернаціоналізація фінансових ринків. Охарактеризовані риси сучасної економіки України: ресурсна структура експорту; незначна складова нематеріальних активів; статичне ставлення до якості. Визначено класифікацію нематеріальних активів підприємства за активами і компетенціями як базу для, прискорення процесу отримання ефекту від господарчої діяльності. Так, вітчизняним підприємствам для реалізації стратегії виходу на європейські ринки необхідно активізувати управління формуванням потенційних можливостей підприємства завдяки розвитку компетенцій персоналу стосовно якості, систем управління та переговорної діяльності щодо залучень додаткових інвестицій, а також сприйняття стандартів якості. На основі вивчення еволюції концепцій управління якістю на підприємстві запропоновано проведення процесу інтеграції систем управління. Ком-плексне використання інструментів управління (спорідненість, зв’язки, терміни роботи): дозволить максимально збільшити синергетичний ефект інтеграції. Практичне значення. Встановлено, що поширення інтегрованих систем управління дозволить: споживачам – отримати товар з максимальним сполученням ціни та якості; власникам бізнесу – сформувати системне ставлення персоналу до якості, партнерам – знизити ризики реалізації угод; суспільству – отримати додаткові джерела фінансування за рахунок збільшення надходжень від експорту переробних галузей та покращити показники екології та безпеки. Перспективи подальших досліджень. Запропоновано напрямок для проведення подальших досліджень щодо запровадження інтегрованих систем управління – пошук економіко-математичних моделей, які оптимально поєднують внутрішні матеріальні активи та нематеріальні активи, що виходять за межі компетенцій окремого підприємства.
Нематеріальні активи та інтегровані системи управління
Keywords: information economy; product competitiveness; product quality; competencies; potential; інформаційна економіка; конкурентоспроможність товару; якість товару; компетенції; потенціал